HALAL INVESTMENT AND TOURISM POLICY IN ACEH PROVINCE, INDONESIA: OPPORTUNITIES AND CHALLENGES - Ardiyansyah, Amzar; Hanifah, Ida; Nadirah, Ida (Universitas Syiah Kuala, 2024)
The Government of Aceh holds the authority to implement halal investment and tourism policies as outlined in Article 25 of Qanun Number 8 of 2013 on Tourism, in conjunction with Article 165 of Law Number 11 of the Aceh Government, which allows for domestic and foreign investment in tourist attraction businesses. However, this authority has not been fully utilized, leading to a negative impact on poverty rates in Aceh. This article employs a normative juridical method, utilizing library research and collecting primary, secondary, and tertiary materials to analyze laws and regulations qualitatively. The current implementation of halal tourism and investment policies in Aceh has not effectively addressed poverty alleviation. Halal tourism is not solely market-driven but also community-driven. Challenges to the implementation of halal tourism include internal factors such as natural disasters, political instability, and institutional management issues, as well as external factors like Islamophobia and marketing perceptions. To address these challenges, the Government of Aceh should establish national and international cooperation programs and strategies to promote the potential of halal tourism. Additionally, a dedicated qanun related to halal investment and tourism should be developed to support these efforts.